Ulva flexuosa subsp. pilifera (Chlorophyta, Ulvophyceae) on the new freshwater locality in Poznań - Rybak, Andrzej; Messyasz, Beata (Instytut Ochrony Przyrody PAN Kraków, 2011)
The research site was located on the flow water reservoir in Poznań (Wielkopolska). The place of U. flexuosa subsp pilifera (Kütz.) Blinding 1963 appearing on the studied area is the 4th inland site of this species in Poland (ATPOL BD09) (Fig. 1). In 2009 the new locality of Ulva flexuosa subsp. pilifera was found in Malta Lake in Poznań City (Fig. 2). Presence of considerable biomass of U. flexuosa subsp pilifera in this freshwater ecosystem was pointed out to the great fertility of the examined water reservoir. The trophic state at the site with U. flexuosa subsp pilifera can result from the fact of the permanent inflow of urban pollutants from Swarzędz, flowing with Cybina river to the examined water reservoir.
Błonica oszczepowata Ulva flexuosa subsp. pilifera (Chlorophyta, Ulvophyceae) na nowym słodkowodnym stanowisku w Poznaniu
Keywords: Ulva; Enteromorpha; freshwater Ulva; Macroalgae; green tides; marine algae; freshwater Enteromorpha; stream; Malta Lake; Malta Reservoir; Ulva in lake; Ulva in river; Ulvaceae; Chlorophyta; Ulva flexuosa subsp. pilifera; Ulva flexuosa; macroalgae mats; maty makroglonowe; zbiornik wodny; Poznań; błonica oszczepowata; błonica; ulwa słodkowodna; błonicowate